Cover Feature: Ordered and Isomerically Stable Bicyclic Peptide Scaffolds Constrained through Cystine Bridges and Proline Turns (ChemBioChem 12/2019). (21st May 2019) - Lin, Ping; Yao, Hongwei; Zha, Jun; Zhao, Yibing; Wu, Chuanliu
Abstract : The cover feature picture shows a bicyclic peptide discovered by panning a home‐made phage display peptide library. In their communication, C. Wu et al. on page 1514 in Issue 12, 2019 (DOI: 10.1002/cbic.201800788 ) explain how they have discovered and identified a class of bicyclic peptides with ordered but irregular secondary structures. These peptides have a conserved cysteine/proline framework for directing the oxidative folding into a fused bicyclic structure consisting of four irregular turns and a 310 helix. This work could inspire the design and engineering of multicyclic peptides with new structures and benefit the development of novel protein binders and therapeutics.